2014
DOI: 10.3839/jabc.2014.056
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidative Effect of Extracts from Different Parts of Kohlrabi

Abstract: Antioxidant activities of ethanol and water extracts of flesh, leaves, and peels of green and purple Kohlrabi were measured by rancimat method, total phenolic compound (TPC), DPPH radical scavenging effect, chelating effect, and reducing power analysis. The highest TPC was observed in ethanol extract from green peel and water extract from purple leaf with 12.00 and 11.70 mg/g of dry sample, respectively. The ethanol extracts from purple Kohlrabi leaf and peel exhibited strong DPPH radical scavenging effects wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…The pigments are located in the meristem skin and consist of cyanidin and cyanidin glucosides which are responsible for the strong antioxidant properties of the species [54][55][56][57]. Examining the antioxidant activity of kohlrabi ethanol and water extracts, Pak et al [241] observed strong DPPH radical-scavenging activity, and purple kohlrabi extracts had higher antioxidant capacity compared to green kohlrabi extracts. Similarly, comparing green and red kohlrabi, Jung et al [242] observed that the latter had double the total phenolic content, as well as a higher antioxidant (DPPH, ABTS, and peroxynitrite scavenging activity assay (ONOO − )) effect compared to green kohlrabi.…”
Section: Other Root Vegetablesmentioning
confidence: 99%
“…The pigments are located in the meristem skin and consist of cyanidin and cyanidin glucosides which are responsible for the strong antioxidant properties of the species [54][55][56][57]. Examining the antioxidant activity of kohlrabi ethanol and water extracts, Pak et al [241] observed strong DPPH radical-scavenging activity, and purple kohlrabi extracts had higher antioxidant capacity compared to green kohlrabi extracts. Similarly, comparing green and red kohlrabi, Jung et al [242] observed that the latter had double the total phenolic content, as well as a higher antioxidant (DPPH, ABTS, and peroxynitrite scavenging activity assay (ONOO − )) effect compared to green kohlrabi.…”
Section: Other Root Vegetablesmentioning
confidence: 99%
“…The pigments are located in the meristem skin and consist of cyanidin and cyanidin glucosides which are responsible for the strong antioxidant properties of the species [47][48][49][50]. Examining the antioxidant activity of kohlrabi ethanol and water extracts, Pak et al [241] observed strong DPPH radical-scavenging activity, and purple kohlrabi extracts had higher antioxidant capacity compared to green kohlrabi extracts. Similarly, comparing green and red kohlrabi, Jung et al [242] observed that the latter had double the total phenolic content, as well as a higher antioxidant (DPPH, ABTS, and peroxynitrite scavenging activity assay (ONOO − )) effect compared to green kohlrabi.…”
Section: Other Root Vegetablesmentioning
confidence: 99%